Probiotics and E. coli infections in man - Lodinová-Zádníková, R; Sonnenborn, U; Tlaskalová, H (The veterinary quarterly, 1998)
After oral administration of live oral vaccines COLINFANT and MUTAFLOR prepared from non-enteropathogenic E. coli strains, both strains colonized effectively the intestine in full-term and preterm infants and remained for many weeks showing, that they were capable to establish themselves as a resident strain in the infant's gut. The presence of E. coli stimulated significantly antibody production in gut, saliva and serum of colonized infants. An early induction of secretory IgA production is important particularly in formula-fed infants, where it partly replaces the lacking immunoglobulin supplied with mother milk. In full-term and premature infants the early presence of non-pathogenic E. coli strains in the intestine decreased significantly the presence of pathogenic bacterial strains in the intestine but also other mucosal surfaces of the body. The COLINFANT strain decreased the number of nosocomial infections, mortality rate in connection with infection, and the need for antibiotics. Both strains replaced successfully pathogenic strains in carriers after treatment with antibiotics.
Keywords: protilátky bakteriální; imunoglobulin A sekreční; Immunoglobulin A, Secretory; Intestines; Immunoglobulin M; aplikace orální; nemoci nedonošenců; Infant, Premature, Diseases; probiotika; Cross Infection; Probiotics; střeva; imunoglobulin M; Infant, Newborn; Escherichia coli; novorozenec; Humans; Antibodies, Bacterial; Bacterial Vaccines; Administration, Oral; Escherichia coli Infections; infekce spojené se zdravotní péčí; bakteriální vakcíny; lidé; infekce vyvolané Escherichia coli